Diabetic Foot Exercises as Physical Activity Therapy to Prevent Chronic Complications of Type II Diabetes Mellitus - Barangkau; Yammar; Eka Hardianti Arafah; Ananda Putri Agustin; Eri Wardanengsih; Ruslang (Journal Of Nursing Practice, 2025)
Background: Type 2 Diabetes Mellitus is still a global health problem. The incidence rate has statistically increased every year. The causes are excessive eating patterns and lack of physical activity, which cause blood glucose levels to be uncontrolled. Uncontrolled blood glucose levels, then chronic complications arise in patients with Type 2 DM, namely diabetic foot ulcers. Therefore, appropriate physical activity therapy is needed to prevent the early emergence of chronic complications of type 2 DM. The right therapy is diabetic foot exercise therapy. Purpose: This study aims to determine the effect of diabetic foot exercise on preventing chronic complications of type 2 DM. Methods: The research design employed is a rigorous pre-experimental design with a one-group pre-test and post-test design. The study population consisted of 20 type 2 diabetes mellitus patients registered at the Tempe Health Center, Wajo Regency. The study was meticulously conducted in the Tempe Health Center area, Wajo Regency, and data were analyzed using a paired sample t-test statistical test with a significant level (p-value <0.05). Results: Diabetic foot exercise therapy is significantly related to changes in ABI values, Diabetic Foot Pain Scale, and GDS in patients with type 2 Diabetes Mellitus before and after therapy. (p-value <0.05). Conclusion: From these findings, researchers concluded that regular diabetic foot exercise holds significant promise. It can effectively increase blood flow to the peripheral parts of the body, control blood glucose levels, and reduce foot pain. This underscores the potential of diabetic foot exercise as a proactive measure to prevent chronic complications of type 2 diabetes mellitus, instilling hope for improved patient outcomes.